Analisis Kepatuhan Kewajiban Perpajakan Pada Pelaku UMKM dan Sosialisasi Peraturan Pemerintah Tahun 2022 di Perkampungan Industri Kecil (PIK) Jakarta Timur - Guntur Ilhamsyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Currently, the Government of the Republic of Indonesia continues to strive and support the empowerment Usaha Mikro, Kecil, dan Menengah (UMKM) in order to strengthen economic stability. The government is very committed to paying attention to the development of UMKM which are currently very developed. It is proven that in 2022 the government provided a lot of stimulus to support the growth of UMKM with a budget allocation of Rp. 400 trillion. This figure, of course, if utilized properly by UMKM entrepreneurs, will have an impact on the development of businesses that are being run by UMKM entrepreneurs. In 2023 the government projects that UMKM will become the national backbone, with the shadow of a recession that is predicted to occur in Indonesia,UMKM are expected to be the way for the revival of the national economy.